Digital maturity models and instruments for vocational high schools in Indonesia - Agus Setiawan; Edhy Sri Yarmanto; Iwan Kustiawan (Jurnal Pendidikan Vokasi, 2024)
Research on digital maturity models in education, particularly vocational education, remains limited, despite the urgent need for schools to adapt to digital transformation. Vocational High Schools (SMK) in Indonesia are mandated to prepare graduates as skilled workers ready to meet industry demands, and therefore require a clear framework to assess their digital readiness. This study aims to develop a model and an instrument to measure the digital maturity level of vocational schools. The research employed a literature review of existing digital maturity models from both education and industry, followed by synthesis and adaptation to the vocational school context. The resulting model consists of five dimensions: strategy and organization, people and culture, products and services, technology and infrastructure, and organizational operations. It defines five levels of maturity: not ready, initial readiness, medium readiness, mature readiness, and fully applied. An instrument with 29 indicators was developed and tested through a pilot study in one vocational school, with results showing strong validity and reliability (Cronbach’s Alpha = 0.935). The findings highlight the inclusion of the products and services dimension as a novel contribution compared to existing educational models. This model and instrument provide practical benefits for vocational school leaders to assess current digital maturity, identify areas for improvement, and plan targeted digital transformation strategies. The study also opens avenues for future research through larger-scale validation and integration of field observations.